Updates in the management of lateral patellar instability - Parker, Amber M.; Hashiguchi, Naofumi; Tanaka, Miho J. (Journal of Joint Surgery and Research, 2025)
The purpose of this study was to review current concepts in the evaluation and management of lateral patellar instability, focusing on anatomical risk factors, diagnostic approaches, and treatment strategies. A comprehensive review of the literature examining anatomical considerations, risk factors, diagnostic methods, and treatment options for patellar instability was conducted. The review focused on the medial patellofemoral complex (MPFC) anatomy, various imaging modalities, and conservative and surgical management approaches. Patellar instability involves multiple anatomical risk factors, including abnormalities in dynamic/static stabilizers, osseous restraints, and lower extremity alignment. The MPFC, consisting of the medial patellofemoral ligament (MPFL) and medial quadriceps tendon–femoral ligament, provides primary restraint against lateral instability in early knee flexion. While 94–100% of first-time dislocations involve MPFL injury and can be managed conservatively, patients with multiple risk factors show 70–90% recurrence rates. Surgical treatment through MPFC reconstruction shows low redislocation rates (1.8–4.5%) and may be combined with additional procedures such as tibial tubercle osteotomy, trochleoplasty, or alignment correction based on individual pathoanatomy. Successful management of patellar instability requires a comprehensive evaluation of anatomical risk factors and individualized treatment approaches. While conservative management is appropriate for first-time dislocations without significant risk factors, surgical intervention through MPFC reconstruction and associated procedures shows promising outcomes in preventing recurrence and improving function in high-risk patients. •Patellar instability is abnormal patella movement from the trochlear groove.•Risk factors are abnormalities in knee stabilizers, bone structure, and limb alignment.•The medial patellofemoral complex (MPFC) stabilizes the patella laterally in early flexion.•Conservative care is appropriate for first medial patellofemoral ligament injuries; high-risk cases often recur.•MPFC surgery reduces instability recurrence.